2020
DOI: 10.1016/j.dsx.2020.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Impact of complete lockdown on total infection and death rates: A hierarchical cluster analysis

Abstract: Introduction and Aims: Retarding the spread of SARS-CoV-2 infection by preventive strategies is the first line of management. Several countries have declared a stringent lockdown in order to enforce social distancing and prevent the spread of infection. This analysis was conducted in an attempt to understand the impact of lockdown on infection and death rates over a period of time in countries with declared lock-down. Material and methods: A validated database was used to generate data related to countries wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
1
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 5 publications
2
61
1
5
Order By: Relevance
“…Another group of studies have used empirical data to retrospectively examine whether NPIs have been effective in reducing transmission, using either statistical methods or mechanistic epidemiological models. Many such studies look at single interventions such as travel restrictions (34) or "lockdowns" (35,36) . Hence they are less useful to policy-makers wanting to establish which of a basket of NPIs are most effective.…”
Section: Discussionmentioning
confidence: 99%
“…Another group of studies have used empirical data to retrospectively examine whether NPIs have been effective in reducing transmission, using either statistical methods or mechanistic epidemiological models. Many such studies look at single interventions such as travel restrictions (34) or "lockdowns" (35,36) . Hence they are less useful to policy-makers wanting to establish which of a basket of NPIs are most effective.…”
Section: Discussionmentioning
confidence: 99%
“…With no doubts, lockdown measures and mobility restrictions were found effective to control the spread of COVID-19 [ 24 ], but, at the same time, showing their harmful consequences on prevention and control of diabetes and other NCDs [ 25 ]. Barone et al., reported that stricter measures against the pandemic may lead to present and future severe impact on diabetes care in South and Central America [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Globally, as of 19 July 2020, there were 14,043,176 confirmed cases of Coronavirus Disease (COVID-19) reported to the World Health Organization (WHO), including 597,583 deaths [ 1 ]. Many countries imposed a stringent lockdown in order to enforce social distancing and prevent the spread of infection [ 2 ]. The use of social distancing, face masks, gloves, and other individual protection measures is having a massive impact on reducing the current peak of active cases but, as recently demonstrated, over time, a decreasing sense of alarm about the pandemic may contribute to a new, larger second wave of epidemics [ 3 ].…”
Section: Introductionmentioning
confidence: 99%